2006
DOI: 10.1136/adc.2005.083881
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory infections in schoolchildren: co-morbidity and risk factors

Abstract: Aims: To assess co-morbidity and risk factors for otitis media, tonsillopharyngitis, and lower respiratory infections in school children. Methods: Logistic regression analysis of co-morbidity and risk factors for airway infections in a population based sample of 10 year old children living in Oslo, Norway. Main outcome measures: otitis media, tonsillopharyngitis, and lower respiratory infections in past 12 months. Results: Airway infections in 10 year old children were common, and significant co-morbidity was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
35
1
12

Year Published

2006
2006
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 31 publications
2
35
1
12
Order By: Relevance
“…High early life incidence as well as high spontaneous recovery rate may reflect that the disease occurs as a natural complication to early pathogen exposure, most likely as part of the gradual maturation of the child's immune system [7]. A number of studies have found AOM to be highly prevalent during early childhood [8], and a recent report has also found AOM common in schoolchildren [9]. In addition, previous studies have shown that early AOM is a risk factor for later AOM and otitis media with effusion (OME) the first few years of childhood [3,6,10,11].…”
Section: Introductionmentioning
confidence: 95%
“…High early life incidence as well as high spontaneous recovery rate may reflect that the disease occurs as a natural complication to early pathogen exposure, most likely as part of the gradual maturation of the child's immune system [7]. A number of studies have found AOM to be highly prevalent during early childhood [8], and a recent report has also found AOM common in schoolchildren [9]. In addition, previous studies have shown that early AOM is a risk factor for later AOM and otitis media with effusion (OME) the first few years of childhood [3,6,10,11].…”
Section: Introductionmentioning
confidence: 95%
“…There are few long-term reports on susceptibility for otitis media in previously operated children [8]. There are many reports on how otitis media affects young children in their first years, but few have focused on morbidity in school children [9,10]. Community-based surveys have been designed to study otitis media in large populations; reported otitis media has been found to be a reliable measure of disease, but reliability of parental reported upper airway surgery has to our knowledge not been evaluated recently [1,11,12].…”
Section: Introductionmentioning
confidence: 98%
“…Moulds take nutrient from the organic matter they rest on, causing deterioration of fabrics, décor and structural materials. While it is difficult to state confidently the direct causal links between mould and ill health (Kolstad et al, 2002), there is a high correlation between the two (Howden-Chapman et al, 2005, Koskinen et al, 1999Karevold et al, 2006), and health literature tends to take a precautionary approach. High concentrations of house dust mites, which do exacerbate respiratory illness, are also associated with high humidity and condensation (Hyndman, et al 2000).…”
Section: Introductionmentioning
confidence: 99%